Regional Growth in Mexico : 1970-1993 - Juan-Ramon, V. (IMF Working Papers; Working Paper ;, 1996)
This paper finds convergence of real per capita GDP in Mexico's states and regions during the period of higher average national per capita growth (1970-85), and divergence during the lower-growth period (1985-93). These results hold across states and regions and within regions. The poorest states and regions grew more than twice as fast as the rest during the first period and experienced absolute and relative decline during the second period. The growth performance of a poor state in relation to the group of poor states was more erratic than the growth performance of a richer state in relation to its group.